2012
DOI: 10.1097/mao.0b013e31825f2365
|View full text |Cite
|
Sign up to set email alerts
|

Facial and Lower Cranial Neuropathies After Preoperative Embolization of Jugular Foramen Lesions With Ethylene Vinyl Alcohol

Abstract: Objective To report three unique cases of cranial neuropathy after super-selective arterial embolization of jugular foramen vascular tumors with ethylene vinyl alcohol. Study Design Clinical capsule report Setting Three tertiary academic referral hospitals Patients Three patients who underwent superselective arterial embolization (SSE) of head and neck paragangliomas with ethylene vinyl alcohol are described. One individual was treated with primary SSE, while the remaining tumors were treated with preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…Gartrell et al highlighted the potential risk of this procedure in their series of 3 patients with postembolization cranial neuropathy. 5 They attribut ed the increased risk of embolization to anatomical varia tions in the cranial nerve blood supply. Another possible explanation is based on the frequently shared external ca rotid artery blood supply between glomus jugulare tumors and the vasa nervosa of the cranial nerves, which renders them vulnerable to occlusion with Onyx during emboliza tion.…”
Section: Discussionmentioning
confidence: 99%
“…Gartrell et al highlighted the potential risk of this procedure in their series of 3 patients with postembolization cranial neuropathy. 5 They attribut ed the increased risk of embolization to anatomical varia tions in the cranial nerve blood supply. Another possible explanation is based on the frequently shared external ca rotid artery blood supply between glomus jugulare tumors and the vasa nervosa of the cranial nerves, which renders them vulnerable to occlusion with Onyx during emboliza tion.…”
Section: Discussionmentioning
confidence: 99%
“…They achieved adequate tumor devascularization but encountered retrograde migration of Onyx into the vertebral artery, which required coil-mediated vessel sacrifice. Gartrell et al 5 reported the first 3 cases of postembolization cranial neuropathies after transarterial Onyx embolization of paragangliomas. In each case, near-complete tumor devascularization was achieved.…”
Section: Murphy and Brackmannmentioning
confidence: 99%
“…1,3,5,6,17,20,25 Its cohesive properties enable the core of the embolic material to propel forward into the tumor vasculature. Compared with earlier embolic materials, Onyx precipitates gradually and has a lower viscosity, which may enable longer, more controlled injections into the tumor nidus.…”
Section: Murphy and Brackmannmentioning
confidence: 99%
See 2 more Smart Citations